Individual dietary specialization and intraspecific morphological divergence of an endemic fish species: the case of Glanidium ribeiroi in the Iguassu ecoregion - Kliemann, Bruna Caroline Kotz [UNESP]; Baldasso, Mara Cristina; Pini, Suelen Fernanda Ranucci; Makrakis, Maristela Cavicchioli; Makrakis, Sergio; Kashiwaqui, Elaine Antoniassi Luiz; Delariva, Rosilene Luciana (Taylor & Francis, 2025)
Because of the importance of information about endemic species and global biodiversity ecoregion, we tested the hypothesis that individuals of Glanidium ribeiroi (endemic species in the Iguassu ecoregion) are specialists and that this specialization decreases with increasing body size, especially concerning the size of the mouth and head, which can be limiting for the quantity and size of prey consumed by smaller individuals. Fish sampling was conducted monthly using gill nets and longlines from 2013 to 2016 in the main channel of the Iguaçu River and two tributaries. We observed the consumption of aquatic insects by smaller individuals and seeds, unidentified fish, and Decapoda by larger individuals. Individual dietary specialization was high and related to head width. The morphological traits of smaller-sized individuals were related to displacement and movement (larger peduncle), and the larger-sized individuals were related to high performance in the exploitation and prey acquisition (larger head and mouth, dorsal eyes, longer intestines). Our results highlight the importance of assessing individual variations within a population, favoring an understanding of population dynamics. In addition, morphological differences may imply differences in the use of habitat and food resources between individuals of larger and smaller body sizes and influence individual specialization.
Keywords: Diet; generalist species; individual variation; morphology; ontogeny